STRESS, A SELF GENERATED PROBLEM-AN AYURVEDIC APPROACH - K, *Babitha; Sivaram, Anjali (International Journal of Ayurveda and Pharma Research, 2018)
In the modern era, the high-tech communication facilities, rapid industrialization, sophisticated life style and extensive use of computers have made lives much easier but they are blamed for making the life stressed. It is estimated that 80% of all modern diseases have their origin in stress. Stress and health are closely linked. Constant exposure to stress leads to psycho-somatic disorders affecting immune, cardiovascular and nervous systems. The diseases linked to stress includes heart disease, asthma, allergies, hypertension, diabetes and even cancer. In view of the changing concepts of health and diseases and with the emergence of modern health hazards, attention has been drawn to the holistic concept of Ayurveda. Ayurveda proclaims that the main purpose of human birth is to attain Purusharthas -Dharma, Artha, Kama and Moksha. To achieve these aims, one needs a healthy body and healthy mind. Ayurveda considers body and mind as inter-related and inter-dependent to each other. Dhi, Dhairya and Atmadi vignynana plays a very important role in the attainment of healthy mind and it in turn contributes a healthy body. Any factor which adversely affects the Sareera, Indriya, Satwa and Athma may lead to ill health either at somatic or psychic level. This review tries to explain how the individuals himself is responsible for stress.